Analisis Kualitas Pelayanan Gadai Kredit Cepat Aman (KCA) pada PT Pegadaian Cabang Pangkep - Atirah Lestari; Ratnawati Ratnawati; Sulkifli Sulkifli (Master Manajemen, 2025)
This research was conducted with the following objectives: (1) To understand the implementation process of the Kredit Cepat Aman (KCA) service program by PT Pegadaian Pangkep Branch, and (2) To assess the quality of service in the implementation of the KCA pawn program by PT Pegadaian Pangkep Branch. This study used two research approaches, namely qualitative and quantitative. The data for the qualitative approach consisted of observation and interview results with research subjects, which were in the form of written or verbal descriptions from observed individuals and actors. Meanwhile, the data for the quantitative approach came from questionnaires and calculations presented in tabular form, processed using Microsoft Excel. The data collection techniques included observation, interviews, questionnaires, and literature study. The results of this study show that: 1) The implementation of the Quick and Safe Credit (KCA) program at PT Pegadaian Pangkep Branch has been carried out properly and in accordance with the standards set by the company, 2) The quality of service, which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, has been met, with 86% of respondents (37 people) selecting the "strongly agree" option on the Likert scale. This score indicates that the service quality at PT Pegadaian Pangkep is in the very good category.